2019
DOI: 10.26650/eor.20197852
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antioxidant and antimutagenic activities of aluminum chloride

Abstract: Purpose: Hemostatic agents are used to control hemorrhage and the gingival crevicular fluid for dental applications. In this study; the antimutagenic and antioxidant activities of aluminum chloride (AlCl3), a topical hemostatic agent used especially in the fields of dermatology and dentistry, were determined. To our knowledge, this is the first study that investigates these properties. Materials and methods: The antioxidant activity was determined by DPPH free radical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“… 2019 ; Sarac et al. 2019 ). The present study showed that the isolated compounds 1 – 4 inhibited α-amylase and thus contributed to the α-amylase inhibition activity of the M. latifolia chloroform extract.…”
Section: Discussionmentioning
confidence: 99%
“… 2019 ; Sarac et al. 2019 ). The present study showed that the isolated compounds 1 – 4 inhibited α-amylase and thus contributed to the α-amylase inhibition activity of the M. latifolia chloroform extract.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with those of previously published studies for both strains regarding treatment with Al. Saraç et al [ 59 ] showed no mutagenic effects in the Ames test for the concentrations of AlCl 3 evaluated (0.025, 0.25, and 1.25 mg/mL plate). In another study, Ahn and Jeffery [ 13 ] verified that Al did not cause mutagenic effects at concentrations of 0.3 and 3.0 mg/L but was suggested as toxic to the TA98 strain.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, it was observed that co-treatments caused the activation of the MAPK/ERK signaling pathway and as a result of this, the progression of the cell cycle was promoted by increasing the phosphorylation of CHK2 in threonine 68, as well as cell migration increased as a result of the high levels of metalloproteases MMP-2 and MMP-9 [ 19 ]. Presumably, the antioxidant activity of AlCl 3 may also have some connection with these findings since it could mitigate ROS induced by chemotherapeutic agents to some degree [ 89 ].…”
Section: Evidence Of Pollutants Affecting the Efficacy Of Chemotherap...mentioning
confidence: 99%